Against All Odds: Tragedy and Statistics - Exe Christoffersen, Erik (Peripeti, 2023)
Against All Odds (2019) are based on identity, representation, and statistics, which portrays how today’s young persons’ lives would statistically look in the future. The question raised by Christoffersen is, how the dramaturgy of the performance creates communication.